Maternal obesity in females born small: Pregnancy complications and offspring disease risk. Issue 1 (6th August 2015) - Mahizir, Dayana; Briffa, Jessica F.; Hryciw, Deanne H.; Wadley, Glenn D.; Moritz, Karen M.; Wlodek, Mary E.
Abstract : Obesity is a major public health crisis, with 1.6 billion adults worldwide being classified as overweight or obese in 2014. Therefore, it is not surprising that the number of women who are overweight or obese at the time of conception is increasing. Obesity during pregnancy is associated with the development of gestational diabetes and preeclampsia. The developmental origins of health and disease hypothesis proposes that perturbations during critical stages of development can result in adverse fetal changes that leads to an increased risk of developing diseases in adulthood. Of particular concern, children born to obese mothers are at a greater risk of developing cardiometabolic disease. One subset of the population who are predisposed to developing obesity are children born small for gestational age, which occurs in 10% of pregnancies worldwide. Epidemiological studies report that these growth‐restricted children have an increased susceptibility to type 2 diabetes, obesity, and hypertension. Importantly during pregnancy, growth‐restricted females have a higher risk of developing cardiometabolic disease, indicating that they may have an exacerbated phenotype if they are also overweight or obese. Thus, the development of early pregnancy interventions targeted to obese mothers may prevent their children from developing cardiometabolic disease in adulthood.